Exploring the Influence of Food and Temperature on North Sea Sandeels Using a New Dynamic Energy Budget Model - MacDonald, Alan; Speirs, Douglas C.; Greenstreet, Simon P. R.; Heath, Michael R. (Frontiers in Marine Science, 2018)
The zooplanktivorous schooling fish sandeels A. marinus comprise a quarter of North Sea fish biomass and are essential food for a number of marine mammals and birds. However, in recent decades there has been a decline in the abundance of older sandeels, with increased overwinter mortality proposed as a contributor. To survive winter animals require a minimum energy reserve which is determined by temperature, prey abundance, and possibly prey size. Here a new dynamic energy budget model is created to determine the influence of food and temperature on sandeel energy dynamics. The model hindcasts changes in energy and survival between 2000 and 2008, a period of pronounced stock decline in the northwestern North Sea. Overwinter starvation mortality was a large contributor towards a recent decline in sandeels in northern UK waters. Highest over-winter mortality rates were recorded for juveniles and not individuals aged 1 or over due to the effect of weight-specific metabolism. However, a sensitivity analysis of the model suggests that mortality rates are more sensitive to changes in copepod abundance in the build up to overwintering rather than temperature during overwintering. Further, projections show that temperature rises are negated by increases in large, but not small copepods. The conclusion is that food-driven size-selective starvation mortality contributed to the northwestern North Sea stock decline and that indirect food web effects of climate change are greater than direct physiological effects on sandeels.